Identifikasi struktur dan ornamen bangunan masjid tradisional Tuha Ulee Kareng Aceh sebagai kearifan lokal - Meutia, Zya Dyena; Araby, Zardan (EMARA: Indonesian Journal of Architecture, 2020)
The Ulee Kareng Tuha mosque is one of the oldest traditional mosques in Aceh, which is still functioning today. However, this building still has various problems, including impaired function, low maintenance of the structure and building materials, and the lack of public knowledge about this mosque's existence. This study aims to identify local wisdom elements in the Ulee Kareng Tuha mosque, especially in the structural components and ornaments that have characterized Aceh in the past. Data collection was carried out by conducting field observations and semi-structured interviews with 15 key informants. The search results show that the mosque's uniqueness can be seen on the roof, which has two levels. The structure and construction of the mosque building are still in original condition with wood materials. Various ornamental carvings that adorn wooden constructions are the embodiment of artistic expression and imply man's relationship with God as the creator. That expression was translated as a form of local wisdom to the Ulee Kareng Tuha mosque building.